Answers

2016-01-12T15:06:44+05:30
Length of hyppotenuse=3 \sqrt{10}
let the smaller leg be x
then,
(hypotenuse) ^{2} = (smallerleg) ^{2} +(longer leg) ^{2}
(3 \sqrt{10} )^{2} = x^{2} +(longer leg) ^{2}
(longer leg) ^{2} =90+ x^{2}
now,
smaller leg=3x
longer leg=(90+[tex] x^{2} ) ^{2} [/tex]
new hypotenuse=9 \sqrt{5}
( 9[tex] \sqrt{5} ) ^{2} [/tex]=9 x^{2} +90+ x^{2} ................................now u can solve

0
2016-01-12T15:15:23+05:30
Smaller leg=3x
longer leg=) ^{2} [/tex]
new hypotenuse=9
) ^{2} [/tex]=9+90+...
0